Nazrul: The Poet Remembered - Kazi, Kalyani (New Delhi : Wisdom Tree, 2009)
Album on the life and times of Kazi Nazrul Islam, 1899-1976, Bengali poet.
"Supported by Public Diplomacy Division, Ministry of External Affairs, Government of India."
English and Bengali.
Keywords: Nazrul Islam, -- Kazi, -- 1899-1976 -- Pictorial works; Poets, Bengali -- Bangladesh -- Biography -- Pictorial works; Poets, Bengali -- 20th century -- Biography -- Pictorial works